Experimental and theoretical evaluation of crystal facet exposure on the charge transfer and SERS activity of ZnO films. Issue 43 (25th October 2022) - Luo, Yuwei; Niu, Lengyuan; Wang, Yifan; Wen, Peipei; Gong, Yinyan; Li, Can; Xu, Shiqing
Abstract : The 0001 and 101̄1 planes exposed on ZnO exhibit a stronger SERS enhancement which is attributed to their enhanced charge tansfer ability and lower surface electronic work function. Abstract : Semiconductors exhibit great potential as a surface enhanced Raman scattering (SERS) substrate due to their low cost, good stability and biocompatibility. However, the extensive application of semiconductors has been restricted by their intrinsically low SERS sensitivity. It is urgently required to design uniform metal oxide substrates with enhanced charge transfer and SERS activity. Herein, three facet–defined (101̄0, 0001 and 101̄1) ZnO films were synthesized via an electrodeposition procedure with the assistance of KCl or ethylenediamine. According to the results, the ZnO films with 0001 and 101̄1 exposed facets exhibit appreciable SERS enhancement factors (EFs) of 1.6 × 10 4 and 2.8 × 10 4 for 4-nitrobenzenethiol (4–NBT), as well as a relatively low limit of detection (LOD) down to 1 × 10 −6 M and 5 × 10 −7 M, respectively. Simultaneously, the electrodeposited ZnO films deliver good repeatability and SERS stability, with relative standard deviation (RSD) less than 6% and 85.2% of their original activity retained after 40 days. Theoretical calculations verified that the 0001 and 101̄1 facets can transfer more electrons from ZnO to the molecules on account of their low facet–related electronic work functions, thus generating the noticeable improvement of SERS activity. The current study provides theoretical and technical support for the crystal facet engineering and property improvement of semiconductors.